Evaluation of the Effects of Postsleeve Gastrectomy Exercise on Long‐Term Glucose Profile and Weight Loss Among Iranian Females: A Prospective Cohort Study From 2016 to 2020 - Mohammad Tayefeh Norooz; Seyed Amir Ahmad Safavi‐Naini; Parnian Jamshidi; Alireza Sadeghi; Mastaneh Rajabian Tabesh; Maryam Abolhasani; Maryam Abbasi; Nasser Malekpour Alamdari; Nathan A. Berger (Health Science Reports)
ABSTRACT Background Weight regain after surgery is linked to an increased risk of relapse for obesity‐related comorbidities, such as type 2 diabetes mellitus (T2DM). This study aims to explore how exercise after laparoscopic sleeve gastrectomy (LSG) affects glucose levels and the percentage of excess body weight loss (%EBWL). Methods In this study, females with non‐insulin‐dependent T2DM who underwent LSG between 2014 and 2015 were enrolled and followed at 1 and 4 years postoperatively in a prospective cohort design. Data on glucose profile, body mass index, and the quality and quantity of exercise were collected. Adequate activity was defined as engaging in more than 150 min of exercise per week. Participants were divided into two groups: the control cohort (low activity) and the exposure cohort (adequate activity). The primary outcomes were %EBWL and glycated hemoglobin (HbA1c). Statistical analysis was performed using paired t‐tests and linear regression in the R programming language. Results The study comprised 246 female participants with a mean age of 46.93 ± 8.07 years, drawn from an initial cohort of 249 individuals. Significant associations were observed between %EBWL, fasting blood glucose, and HbA1c with the intensity of exercise. The active cohort exhibited superior outcomes in terms of %EBWL (78.1 ± 22.06 vs. 28.1 ± 10.9), reductions in HbA1c (−0.37% vs. −0.01%), and a decrease in body mass index (−11.6 vs. −8.46 kg/m²). The following formula was established to predict %EBWL at 48 months based on exercise levels (R2 = 0.86): %EBWL (at 48‐month) = −5 (if no exercise at all) + 1*exercise time (minutes/day) + 10*exercise frequency (session/week). Conclusion This study highlights the essential role of postoperative exercise in facilitating long‐term weight loss and modest improvements in glucose profiles. The developed formula effectively predicts %EBWL based on the patient's exercise profile, thereby emphasizing the significance of physical activity and patient engagement in attaining sustained positive outcomes. It is recommended that patients receive guidance on maintaining an active exercise regimen.